Mindful partnering: implications of a novel theoretical construct for predicting reduced reactivity to marital conflict, greater physical health, and lower mortality risk - Seiter, Natasha, author; Lucas-Thompson, Rachel, advisor; Quirk, Kelley, committee member; Prince, Mark, committee member; Haddock, Shelley, committee member (Colorado State University. Libraries, 2022)
According to the theory of allostatic load, chronic stress leads to damage on the body that contributes to problems with physical health and early mortality. A large body of research suggests that mindfulness reduces stress, health problems, and mortality risk. In addition, stressful relationships with intimate partners have the power to cause frequent and/or intense physiological responses that, over time, contribute to allostatic load and thus negative health and mortality outcomes. However, previously identified predictors of relational and thus physical health lack a unifying concept to synthesize them. Study 1 presents the conceptualization of a novel theoretical construct, mindful partnering, as interpersonal mindfulness with ones' romantic partner, as well as initial validation of the Mindful Partnering Measure (MPM). Participants were 599 individuals from: 1) an undergraduate student sample recruited from a university subject pool [used for exploratory factor analyses (EFA), N= 335] and 2) a sample of married adults recruited through Mechanical Turk [used for confirmatory factor analyses (CFA), N= 264, subsets used for construct validity N= 147, and test-retest analyses N= 53]. Results of the EFA and CFA supported a five-factor structure. Tests of internal consistency, construct validity, and test-retest reliability in the sample of married adults provided evidence for reliability and validity of the total MPM to assess mindful partnering, as well as the Mindful awareness and Acceptance/compassion subscales. However, the other subscales did not demonstrate adequate test-retest reliability. Use of this measure in further research will allow for the study of the potential correlates and benefits of mindful partnering to further our understanding of this novel construct, and the following studies utilized the total and validated subscales of the MPM. Study 2 investigated whether higher levels of mindful partnering would be associated with lesser biological stress to relationship conflict. Seventeen couple pairs (N= 34) visited the laboratory to complete several tasks, including questionnaires (e.g., the MPM) and a conflict discussion. Participants had their Respiratory Sinus Arrythmia (RSA), a measure of parasympathetic nervous system activation, measured during the baseline period and conflict discussion. Regression analyses suggested that MPM-Mindful awareness significantly predicted partners' greater RSA during the discussion task, with a small effect, suggesting greater physiological relaxation. No other results were significant, however, there were greater-than-trivial effects for several associations between mindful partnering variables and RSA, as discussed. In general, results suggested that when one's partner is more mindful, it may soothe the nervous system and relieve the potential stress of marital disagreement, however, practicing mindful partnering may actually be associated with biological stress. Study 3 examined associations among mindful partnering and physical health as well as telomere length, an indicator of cellular aging. Eighty-three (N= 166) couples completed questionnaires (including the MPM as well as an item to measure overall physical health), and 43 (N= 86) of these couples gave a saliva sample which was assayed for telomere length. Results of regression analyses demonstrated that self-health was associated with total mindful partnering as well as MPM-Acceptance/compassion, which was also associated at trend levels with partner health. Links between total mindful partnering and MPM-Acceptance/compassion with health variables, as well as between MPM-Mindful awareness and partner health also demonstrated greater-than-trivial/small, positive effect sizes. Associations between mindful partnering and telomere length did not reach significance, however, there were greater-than-trivial effect sizes for associations between self telomere length and MPM-Mindful awareness in the negative direction and MPM-Acceptance/compassion in the positive direction, and partner telomere length showed a small positive effect with MPM-Mindful awareness. These findings suggest that long-term health may be improved through mindful partnering, with implications for couples therapy and other interventions for couples.
Keywords: marriage and family therapy; mindfulness; telomere length; measurement; couples; respiratory sinus arrythmia